Experimental evidence on the drivers of index-based livestock insurance demand in southern Ethiopia - Takahashi, Kazushi; Ikegami, Munenobu; Sheahen, M.; Barrett, Christopher B. (Elsevier, 2016)
While index-based microinsurance has attracted considerable attention, uptake rates have been weak in many low-income countries. We explore the purchase patterns of index-based livestock insurance in southern Ethiopia, focusing on the role of accurate product comprehension and price. We find that randomly distributed learning kits improve subjects’ knowledge of the products; however, we do not find strong evidence that the improved knowledge per se causes greater insurance uptake. We also find that reduced price due to randomly distributed discount coupons has an immediate, positive impact on uptake, without dampening subsequent period demand due to reference-dependence associated with price anchoring effects.